Implementación de la Contabilidad en la Empresa “Global Pernos” de la ciudad de Loja. Período del 01 de octubre al 31 de diciembre del 2021 - Cabrera Pizarro, María Belén (2023)
The curricular integration project entitled "IMPLEMENTATION OF ACCOUNTING IN THE COMPANY "GLOBAL PERNOS" OF THE CITY OF LOJA, PERIOD FROM OCTOBER 01 TO DECEMBER 31, 2021", was developed in order to implement commercial accounting, which allows keep an orderly and detailed record of the activities that are generated in the company, in order to provide a significant contribution of real information to the owner, with which he can analyze and take timely decision for the business’ benefit To implement accounting in the company Global Pernos Co.an accounts plan was initially structure according to the needs of company it served as the basis for the preparation of the Accounting Manual. Next, the source documentation was collected and classified in orderly manner giving way to the detailed record of the invoices in sales assistants and purchases assistants, which facilitated the control and consolidation of the operations realized. Subsequently, the Initial Inventory was prepared through physical verification, allowing to determine the Assets, Liabilities and Equity of the company; it served for the preparation of the Initial Accounting Statement and to start the jornalization of all transactions in the Daily Book, to transfer the values to the General Ledger and obtain the balances of each account that allowed the elaboration of the Trial Balance. The corresponding adjustments were made and the Work sheet was prepared, obtaining the Financial Statements, where the real economic and financial situation of the company Global Pernos, is reflected It culminated with the presentation of the conclusions and recommendations considered pertinent for the implementation of accounting in the company Global Pernos, factors that, if accepted and welcome by the owner will be great contribution to the growth and permanence of the business since it will allow maintenance, adequate record, control and consolidation of the operations carried out and therefore know the real economic and financial situation of the company for good decision making. With the accounting implementation, an order and control were allowed to establish in their daily operations through accounting records, in addition to know the economic reality of the company, which will serve as a basis for making decisions that improve shortcomings and generate greater utility and benefits.